Respuesta :

Answer:

y=3

x=2

Step-by-step explanation:

Making substitution

y+7=5x

y=5x-7

Substituting the y into the other equation

-3x-2(5x-7)=-12

-3x-10x+14=-12

-13x=-14-12

-13x=-26

x=2

We have x=2 then substitute it into the first equation

y+7=5(2)

y+7=10

y=10-7

y=3

So the answer is

y=3

x=2

Answer:

x=2 and y=3

Step-by-step explanation:

After solving, you can check your work by substituting the values of x and y into the equations and solving for them.

3+7=10

10=10

-6-6= -12

-12 = -12

ACCESS MORE